The Impact of a Multifaceted Intervention on the Rate of Preventive Services Offered in a Student-Run Clinic - Menning, Melanie; Nabower, Aleisha; Medder, Jim; Geske, Jenenne; Margalit, Ruth (Journal of Student-Run Clinics, 2016)
Background: The importance of preventive services has been well established, yet rates of preventive service delivery continue to lag behind national goals. While numerous studies have identified barriers to preventive service delivery and implemented interventions to improve delivery, research into this important area is lacking in the setting of student-run clinics. Methods: In this study a multifaceted intervention consisting of patient and provider education, provider check list, pre-clinic chart review, and financial assistance for preventive services was implemented for 14 months in a student-run clinic. Results: Rates of delivery of United States Preventive Services Task Force (USPSTF) Grade A and B recommended preventive services were evaluated before and after implementation of the intervention with 16 of 26 services improving during the intervention but only tetanus immunization reaching significance. In addition, rates of delivery of preventive services were compared to reported national averages and targets set by Healthy People 2020 with 16 of 20 services being offered at or above reported national averages and 10 of 16 services meeting the targets laid out in Healthy People 2020. Conclusions: The rate of preventive services can be improved in student-run clinics through the implementation of multi-faceted interventions to a level that meets national averages and targets.